Wellhead Growth Evaluation and Analysis with Stiffness Method; an Onshore Gas Well Case Study - Ganesha R Darmawan (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2020)
One of the challenges in designing a production or an injector well is the potential of wellhead growth primarily because of casings thermal stress that are connected to the wellhead. Well integrity issue could occur if this movement was not addressed correctly. Casing thermal stress was created by temperature change in production or injection gas or fluids. That temperature change induces uncontrolled heat transfer from tubing to the casing strings in form of casing thermal stress.One of gas field in Indonesia was producing gas with formation water. One well was showing significant wellhead growth during production. The hazard noticed was the stiffness of the surface flowline equipment, as the wellhead moving upward, but the flowline is not free to move. The flange connection between the Christmases tree manifold to the flowline was the weak point, causing the well has to be shut in for further investigations.Well constructions data collection continued with analysis was performed with  stiffness method in multistring well thermal growth model  as explained and developed by Q. Jim Liang[1] to calculate casing thermal stress and wellhead growth. Thermal growth is sensitive to the length of free moving casing sections, as the heat transfer laterally to the casing strings. This paper will evaluate and analyze the cause of wellhead growth on gas production well with stiffness method in multistring casing, and estimating the cement column height on the casings that might cause the measured movement.  A sensitivity of top of cements intermediate and production casing and how it affects the wellhead growth and thermal force. And also comparison forces between   annulus pressure and temperature will also discussed in this paper.